Supply chain coordination by contracts considering dynamic reference quality effect under the O2O environment. (January 2022) - Qiu, Ruozhen; Yu, Yue; Sun, Minghe
Highlights: Study O2O supply chain coordination with dynamic reference quality effect. Use wholesale price, cost-sharing and two-part tariff contracts for coordination. Transform the developed dynamic models with the three contracts to tractable forms. Compare equilibrium solutions among the three contracts. Perform numerical studies to verify the results and to provide managerial insights. Abstract: This study investigates the coordination problem for a two-tier decentralized supply chain consisting of a supplier and a retailer. The supplier can control and adjust the product quality and the retailer sells the product both offline and online (O2O) to consumers with reference quality effect. The market demand is dependent on the retail price and on the consumer reference quality effect that is a dynamic function of past product quality. The problem is modeled as a Stackelberg game with the supplier as the leader and the retailer as the follower. The wholesale price (WP), cost-sharing (CS) and two-part tariff (TP) contracts are used to coordinate the decentralized supply chain. Using the Hamilton-Jacobi-Bellman equation, the dynamic optimal control models are transformed into tractable models to obtain the equilibrium solutions. The results show that the decisions of the supply chain members are dynamic and depend on the consumer initial reference quality, the reference quality effect strength and the memory parameter. The retailer should attract potential consumers with dynamic reference quality effect to purchase the product offline. The TP contract can coordinate the supply chain and can benefit the supplier, the retailer and the consumers. As compared with the WP contract, the CS contract can improve the performance of the supply chain. These results are verified through numerical experiments. The impacts of the major parameters, including the reference quality effect strength, the consumer memory parameter, the cost-sharing rate, the discount rate and the offline consumer rate, on the equilibrium solutions and on the profits of the supply chain members are also examined through numerical experiments.